Venture Capital Investments Models in Russia and the USA as Key Factor for Development of Innovative Enterprises - A. G. Philippov; E. V. Gruzdeva (Модернизация, инновация, развитие, 2019)
Purpose: this article aims to determine key characteristics features of venture capital investments models in the context of the development of innovative enterprises. For this purpose the authors conducted analysis of the current state and key differences of venture capital investments models in Russia and in the USA, determined fields and ways for further improvement of domestic models of venture capital investments.Methods: to achieve the stated goal, theoretical research methods - abstraction, analysis and synthesis were used. Adoption of these methods, led to analysis of the theoretical basis of venture capital investments models and identification of key features having the greatest practical significance. The models of venture capital investments in Russia and the USA were studied, and a quantitative and qualitative comparative analysis of the elements characterizing the models of venture capital investments was carried out. The study was based on the data published by the national associations of venture investors and the information database of venture capital companies Pitchbook.Results: this article reveals the importance of venture capital investments as the main factor affecting the innovative development of the Russian economy. In modern conditions, venture capital investments are a key tool that helps bring financial resources to young innovatively active companies. This article summarizes results of the study of the theoretical base of venture capital investments models and the historical dynamics of venture capital investments in Russia and the USA. A comparative analysis revealed similarities and differences between the following elements, characterizing the models of venture capital investments in Russia and the USA: stages of development of venture capital companies, types of investors and sources of venture financing, distribution of venture investments by industry, exit strategies and organizational forms of venture capital investments. The paper as well summarizes fields and ways for further improvement of models of venture capital investments based on a comparative analysis.Conclusions and Relevance: based on the conducted research and comparative analysis of venture capital investment models in Russia and the United States, the proposals for further improvement of Russian venture capital investment models were developed and presented in the article.